O contrato de compra e venda com reserva de domínio e a indenização decorrente de sua resolução - Azevedo, Lúcio Flávio Moraes de (Universidade do Vale do Rio dos Sinos, 2013)
The social life has improved and become more and more enjoyable with the convenience provided by the numerous goods that knowledge and technology enabled to develop. But man, with his singular effort can´t produce anything. Only through the exchange of operations do we have access to the goods available. So, each one supplies their work to produce goods. This allows others to acquire what they need to produce and, with the fruit of their labor, get what they yearn. Buying and selling, in this context shows its extreme importance, it´s is the contractual form most used in this exchange of operations and circulation of wealth is produced. Through this, a subject provides the acquisition of a good, for what the other attains respective payment, substantiated in the price. Occurs that not everybody has the entirety of purchase price for the intended object. On the other hand, it is the interest of the holder to sell it, so you can buy other things that are necessary. At this juncture, a solution presents itself as to buy and sell on credit, a modality by which one part attains a certain item and the other allows you to pay the price in deferred installments in time. However, the seller is faced with the problem of ensuring that the buyer will pay all the installments. The solution given by the law is the constitution guarantee on their own good. Thus, it equalizes the issue, reaching the buyer the possession and ownership resolvable. It remains to the seller the area, on the transfer under condition precedent to the payment of the price, when the acquirer merges possession and control. Finalizing the contract for payment, it will be all right by the law. However, if the buyer delays its installment, the seller may terminate the contract, performing search and seizure of the good. It will remain, in this case, the indemnity for damages expressly contained in the law, in addition to those that the law requires the interpretation of legal ones. It is the compensation of the entirety harm experienced by the buyer, of interest to this study.
Keywords: Contrato; Compra e venda; Reserva de domínio; Garantia; Coisa infungível; Mora; Inadimplemento; Resolução; Indenização; Danos; Contract; Buying and selling; Domain booking; Warranty; Linfungible thing; Live; Default; Resolution; Damages